Work life balance among PERKESO employee: external and internal conflicts affecting job satisfaction / Mohamad Yazid Mohamad Hepni - Mohamad Hepni, Mohamad Yazid (2023)
The purpose ofthe study was to examined and compared the relationship ofthe work-life balance among SOCSO (Social Security Organization) employees and how external and internal conflicts can influence their job satisfaction. SOCSO, a government body in charge of social security protection in Malaysia, could encounter issues with workers' ability to combine work and personal obligations. Work-life balance is an important aspect of a healthy work environment. Maintaining a work-life balance helps reduce stress and helps to prevent burnout in the workplace. Work-life balance is crucial for organizations managing highly technical professionals since their dedication and devotion are essential to the organization's success. The study was carried between April 2023 until December 2023. In this study, the researcher used quantitative research method. Quantitative research involves collecting and analyzing numerical data. It is ideal for identifying trends and averages, making predictions, testing relationships, and generalizing results for large populations. Anyone may be inspired to take the required actions to achieve a healthy work-life balance by realising how important it is to do so. A healthy work-life balance benefits both the organization / company and the people. The productivity, morale, and physical health of employees may all be improved by striking a balance between work and personal life. We should all prioritise finding a work-life balance. A lack of balance in any one of these areas will make life difficult and provide several risks to one's health, happiness, and emotional stability.